Optimisasi Biaya Transportasi Pengiriman Paket Jalur Nugraha Ekakurir di Sumatera Utara dengan Russel Approximation Methode(RAM) - Banurea, Yana Wiranta; Sari, Rina Filia (Jurnal Pendidikan Matematika : Judika Education, 2024)
The aim of this research is to examine the optimization of transportation costs for sending packages on the Nugraha Ekakurir route in North Sumatra using the Russell Approximation Method (RAM). This research is quantitative research conducted at This research was conducted at the JNE Company, Medan Main Branch. Based on the research results, to optimize transportation costs for sending JNE packages in North Sumatra using the Russell Approximation Method, the overall cost allocation is much lower. Based on the test results, the initial solution obtained using the Russell Approximation Method achieved optimal solution results. The conclusion from the results of this research was that transportation costs decreased by 13.4%. The resulting optimal cost is Rp. 9,262,700 and initial costs of Rp. 10,700,000. Keywords: Optimization, Distribution Costs, Russell Approximation Method